Largely improved electromechanical properties of thermoplastic polyurethane dielectric elastomers by the synergistic effect of polyethylene glycol and partially reduced graphene oxide. (12th April 2017) - Ning, Nanying; Li, Shangqing; Sun, Haibin; Wang, Yong; Liu, Suting; Yao, Yang; Yan, Bingyue; Zhang, Liqun; Tian, Ming
Abstract: In this study, moderate content of polyethylene glycol (PEG) with ionic conductivity and low content of graphene oxide (GO) were simultaneously introduced into thermoplastic polyurethane (TPU) followed by in-situ chemical reduction of GO (rGO) to prepare TPU/PEG/rGO dielectric elastomer (DE) composites with largely improved electromechanical performance. The results showed that PEG remarkably disrupted the hydrogen bonds between TPU chains in TPU/PEG/rGO composites and formed new hydrogen bonds with TPU. In addition, PEG molecules can also form hydrogen bonds with rGO, leading to the coating of PEG on GO and thus the separation of rGO from TPU. Interestingly, PEG and rGO showed significant synergistic effect on the dielectric constant ( ε′ ) of the composites, resulting in the large increase in ε′ at 10 3  Hz from 7 for pristine TPU to 71 for TPU/PEG/rGO composite. This was attributed to the increase in dipole polarizability of TPU chains caused by the disruption of hydrogen bonds and the increase in interfacial polarizability caused by the favorable electron transfer from partially reduced GO coated by PEG to TPU. The elastic modulus ( Y ) of the TPU/PEG/rGO composites largely decreased because of the plasticizing effect of PEG and the separation of GO from TPU. Owing to the simultaneous increase in ε′ and decrease in Y, the composite showed 49 times increase in electromechanical sensitivity ( β ) and 6.5 times increase in actuated strain at a certain electric field over that of pristine TPU.